Metacognitive awareness of cognitive problems in schizophrenia: exploring the role of symptoms and self-esteem. Issue 3 (5th June 2013) - Cella, M.; Swan, S.; Medin, E.; Reeder, C.; Wykes, T.
Abstract : Background: People with a diagnosis of schizophrenia have limited metacognitive awareness of their symptoms. This is also evident for cognitive difficulties when neuropsychological assessments and self-reports are compared. Unlike for delusions and hallucinations, little attention has been given to factors that may influence the mismatch between objective and subjectively reported cognitive problems. Symptom severity, and also self-esteem and social functioning, can have an impact on cognitive problem perception and help to explain the gap between objective and subjective cognitive assessments in psychosis. Method: One-hundred participants with a diagnosis of schizophrenia were recruited and assessed with a comprehensive neuropsychological battery, a measure of awareness of cognitive problems and measures of psychotic symptoms, social and behavioural functioning and self-esteem. Regression was used to investigate the influence of symptoms, social functioning and self-esteem, and patients with different levels of cognitive problem awareness were contrasted. Results: Simple correlation analysis replicated the lack of association between objective cognitive measures and metacognitive awareness of cognitive problems. However, the results of the regression analyses highlight that self-esteem and negative symptoms predict metacognitive awareness. When significant predictors were controlled, individuals with better awareness had more impaired working memory but higher IQ. Conclusions: Poor self-esteem and high negative symptoms are negatively associated with metacognitive awareness in people with schizophrenia. Interventions that aim to improve cognition should consider that cognitive problem reporting in people with schizophrenia correlates poorly with objective measures and is biased not only by symptoms but also by self-esteem. Future studies should explore the causal pathways using longitudinal designs.